Interação genótipo x ambiente para peso aos 365 dias em bubalinos da raça Mediterrâneo - Rodrigues, Fernando Barreto; Carneiro, Paulo Luiz Souza; Ramos, Alcides De Amorim; Ambrosini, Diego Pagung; Malhado, Carlos Henrique Mendes (Embrapa Secretaria de Pesquisa e DesenvolvimentoPesquisa Agropecuária Brasileira, 2015)
Abstract: The objective of this work was to verify the presence of the genotypes x environments interaction (GxE) for weight at 365 days of age in the Mediterranean breed of buffaloes, using models of reaction norms through random regression. The standard animal model and the models of reaction norms were tested, and the hierarchical model reaction norm (MRN) was evaluated with one and two steps. The homoscedastic hierarchical model of reaction norms with one-step (HMRNHO1s) had the best fit, based on three criteria for comparison. The direct heritability estimates for this model ranged from 0.19 to 0.78, with environment improvement. Besides, direct breeding values (scale effect) changed for some breeders, which indicates the existence of GxE interaction. The Spearman correlations were high, both in the comparison between the standard animal model and MRN, as in the comparison between low, medium, and high management levels in HMRNHO1s. Therefore, although there is GxE interaction, the ranking of breeding animals is not significantly affected by the models. The majority of buffaloes is formed by animals with robust genotypes, which are less sensitive to environmental changes.

Resumo: O objetivo deste trabalho foi verificar a presença da interação genótipos x ambientes (GxA) para peso aos 365 dias de idade, em bubalinos da raça Mediterrâneo, com o uso de modelos de normas de reação via regressão aleatória. O modelo animal padrão e os modelos de normas de reação foram testados, tendo-se avaliado o modelo hierárquico norma de reação (MNR) com um e com dois passos. O modelo hierárquico homocedástico de norma de reação com um passo (MHNRHO1P) apresentou o melhor ajuste, com base em três critérios de comparação. As estimativas de herdabilidade direta para esse modelo variaram de 0,19 a 0,78, conforme a melhoria do ambiente. Além disso, houve mudança dos valores genéticos diretos (efeito escala) de alguns reprodutores, o que indica a existência de interação GxA. As correlações de Spearman foram altas, tanto na comparação do modelo animal padrão com os MNR, como na comparação entre os níveis de baixa, média e alta qualidade no MHNRHO1p. Portanto, embora haja interação GxA, a classificação dos reprodutores não é significativamente afetada pelos modelos. A maioria dos bubalinos é formada por animais de genótipo robusto, que são menos sensíveis a mudanças ambientais.
Genotype x environment interaction for weight at 365 days in Mediterranean buffaloes
Keywords: scale effect; environmental gradient; hierarchical model; reaction norms; random regression; breeding value; efeito escala; gradiente ambiental; modelo hierárquico; normas de reação; regressão aleatória; valor genético